Penerapan Media Gambar Seri Dengan Teks Pendamping Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas II SDN Sonit - Suparta Abuhu; Ayubi Cakradiwati (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This one-cycle classroom action research (two meetings) aimed to improve the early reading skills of second-grade students at SDN Sonit through the implementation of picture series media with accompanying texts. The learning activities were carried out in four stages: planning, implementation, observation, and reflection. The research subjects consisted of 21 students. The instruments used included tests of reading accuracy, reading speed (words per minute), literal comprehension, and a checklist of reading errors (substitution, omission, and inversion). The results showed an increase in the total score from 58.6 in the pre-action stage to 73.2 in the first meeting and 81.9 in the second meeting. Reading speed improved from 37 to 60 words per minute. The use of picture series with accompanying texts helped students understand story sequences and connect sounds with meaning, thereby improving reading fluency without reducing accuracy. These findings suggest that integrating relevant visual and textual elements can serve as an effective alternative strategy for teaching early reading in lower elementary grades.